Impact of Managerial Entrenchment on Financial Flexibility and Leverage of Small Public Firms: Policy Implications for Global Economic Crisis (Global Journal of Management and Business Research, 2023)
This paper examines the impact of managerial entrenchment on financial flexibility and financial leverage decisions of small public firms compared to medium and large firms We group firms into market capitalization quartiles where small public firms are within the first medium firms are between the first and second and large firms are above the third quartile Results show that entrenched managers in small firms hold significantly less excess cash than entrenched managers in medium or large firms Small public firms borrow significantly more money using short-term maturity compared to medium and large size firms which borrow less money using long-term maturities Compared to pre-2008 crisis levels most firms borrowed more money and held more excess cash during and after the global economic crisis though small firms had limited access to cheap long-term funding compared to medium and large firms Managers adopted more antitakeover practices after the 2008 global crisis and they became more entrenched Results have economic and policy implications Public policy should prioritize timely within 1 5 to 2 years access to cash for small firms over medium and large firms to pre-crisis excess cash levels in a global economic crisis
Keywords: managerial entrenchment; financial flexibility; financial leverage; debt maturity; excess cash; small firms